IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA PEMBELAJARAN IPA KURIKULUM MERDEKA: STUDI ANALISIS KASUS - Nisa, Husnul; Artika, Wiwit; Andayani, Dewi; Samingan, Samingan; Rahmatan, Hafnati (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Differentiated learning is a strategy that customizes learning content, processes, and activities to accommodate the diverse needs of students. It is a key approach for addressing the varied learning styles and abilities within a classroom. This study aims to identify the categories of differentiated learning module design, the implementation of differentiated learning, and the opportunities and challenges faced by teachers. The research uses a qualitative approach with a survey research design. The population consists of all science teachers at SMP Negeri 2 Banda Aceh, totalling five individuals. This study used a total sampling technique. The research parameters include categories of differentiated learning module design, categories of differentiated learning implementation in classroom, and the opportunities and challenges encountered by teachers. Data analysis was conducted using percentage calculations based on Guttman scale scoring. The results show that the science teachers’ differentiated learning modules have an average score of 86%, which falls into the good category. The implementation of differentiated learning reached 96.6%, classified as very good. Teachers viewed differentiated learning as providing opportunities to improve learning outcomes, student engagement, the use of technology, and the development of teacher competencies. However, the obstacles faced included difficulties in adjusting to student needs, limited resources, and unequal access to technology.